ANALYST STUDY AND OPTIMIZATION OF LIGHT TRUCK CAB FLOOR STRENGTH - ZHAO MinQing; LU YuMing; CHEN WenGang; LIN ZhenWen; DONG YongFeng; CHEN MingLiang (Jixie qiangdu)
Based on the background of frequent cracking failures of the cab floor of a light commercial truck,the cause analysis and optimization designs of the strength of the cab floor of this brand commercial vehicle were carried out. First,the CAE modeling and simulation of the light truck floor cab were carried out,and the time domain data onto the strain of each measuring point of the road driving of the light commercial truck was measured using the electrical measurement method. The calculation results show that the stress extreme value of the CAE calculation simulation results reaches 160. 7 MPa,and the stress extreme value of the same part measured by the electrical measurement method reaches 250. 3 MPa,which is far beyond the yield strength limit of the cab material. Then,on this basis,the nature of the problem is judged,and the force analysis and calculation are carried out on the turning mechanism. The calculation results show that the theoretical difference between the torque limits of both sides is only 3 424. 2 N·m,and the reason for the crack is that the strength of the cab body is too low. Finally,on the basis of experiments and theoretical analysis,this paper proposes two structural strength optimization measures,including strengthening plates and welding seams,and adding structural adhesive,and conducts comparative analysis in various aspects to provide a reference for the subsequent engineering structure optimization and strength analysis.